2020
DOI: 10.1038/s41550-020-1018-2
|View full text |Cite
|
Sign up to set email alerts
|

An eclipsing substellar binary in a young triple system discovered by SPECULOOS

Abstract: corresponding authors Mass, radius, and age are three of the most fundamental parameters for celestial objects, enabling studies of the evolution and internal physics of stars, brown dwarfs, and planets. Brown dwarfs are hydrogen-rich objects that are unable to sustain core fusion reactions but are supported from collapse by electron degeneracy pressure [1]. As they age, brown dwarfs cool, reducing their radius and luminosity. Young exoplanets follow a similar behaviour. Brown dwarf evolutionary models are rel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 64 publications
3
24
0
Order By: Relevance
“…i This companion was noticed by Triaud et al (2020) in the Gaia DR2 as equidistant and co-moving companion of the brown dwarf 2M 1510 A, which is listed in the EPE, consistent with our results. j KELT-23 B was first discovered by (Johns et al, 2019) with Keck/NIRC2 AO imaging, who used Gaia DR2 astrometry to prove the equidistance and common proper motion of the companion with the exoplanet host star KELT-23 A, as done in this study.…”
Section: Detected Companions Of Exoplanet Hostssupporting
confidence: 88%
“…i This companion was noticed by Triaud et al (2020) in the Gaia DR2 as equidistant and co-moving companion of the brown dwarf 2M 1510 A, which is listed in the EPE, consistent with our results. j KELT-23 B was first discovered by (Johns et al, 2019) with Keck/NIRC2 AO imaging, who used Gaia DR2 astrometry to prove the equidistance and common proper motion of the companion with the exoplanet host star KELT-23 A, as done in this study.…”
Section: Detected Companions Of Exoplanet Hostssupporting
confidence: 88%
“…The 10-Gyr isochrone is indicated by the black dashed line, and NGTS J0930-18 B by the red triangle. Similar M-dwarfs fromParsons et al 2018, Triaud et al 2020and Mireles et al 2020 are shown in Black.…”
supporting
confidence: 75%
“…Two years ago, we knew of only 17 transiting BDs (and 2 BDs in an eclipsing binary system discovered by Stassun et al 2006), and only 14 of those with uncertainties on their radius at less than 10%. Now, we know of 25 BDs that transit a star (and 3 additional BDs in a triple system discovered by Triaud et al 2020), and as we show in Table 6, the TESS mission has made a steady contribution to the number of known transiting BDs over the span of its primary mission. Five of six of these TESS BDs also have improved precision on the measurements of their radii thanks to improved parallaxes from Gaia DR2.…”
Section: Discussionmentioning
confidence: 90%